PROGRAM PENENTUAN PROPORSI SAHAM PORTFOLIO MENGGUNAKAN QUADRATIC PROGRAMMING WOLFE - Ngarap Imanuel Manik; Elvia Yoe (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Investors generally desire substantial returns from their investments with minimal risk of loss, and they invest their capital in several types of stocks (stock diversification). The problem that then arises is how they determine the proportion of stocks in their portfolio that will provide a large return (profit) with minimal risk. To solve this problem, the author will implement Quadratic Programming using the Wolfe method to determine the optimal portfolio proportion for investment. Several examples of Quadratic Programming calculations using the Wolfe method performed with the help of a computer program are presented in this paper. The results obtained show no significant difference from the results of manual calculations.